Implementasi Perjanjian Bagi Hasil Antara Pt. Bagus Sukses Sejahtera Dengan Peternak Ayam Broiler - I Gede Putu Laba Sepriyadi Sudhiarsana (Fakultas Hukum Universitas Mataram, 2022)
The aims of this work are to know substances of the results sharing agreement and its partnership implementation and also to know risks responsibilities of the partnership agreement between PT. Bagus Sukses Sejahtera and broiler farmer. Type of this work is normative empiric legal results. After conducting a series of research, it can be concluded that, first of all, results sharing partnership agreement substances between company and farmer has been in line with Indonesian law which been mentioned on the rights and duties of both parties during the time of chicken rearing. Secondly, implementation of the agreement also in align with the concluded agreement between parties. In addition, regarding results sharing, farmer will get benefit from the gap of prices seeds, feed, medicines supplied by the company and the company benefits from chicken seeds, feed and medicines supplied to farmers.